2016
DOI: 10.1016/j.jasrep.2016.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotope evidence of juvenile foraging in prehistoric Central California

Abstract: Ethnographic evidence demonstrates that hunter-gatherer children may forage effectively enough to supplement an adult provisioned diet, where ecology, subsistence strategies, and social organization are conducive to juvenile participation. We use stable isotope measures (δ 15 N and δ 13 C) from bone collagen and serial-samples of dentinal collagen extracted from first molars to examine childhood dietary patterns among 24 individuals from the Late Holocene Central California site CA-ALA-554. We identify weaning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 50 publications
2
23
0
Order By: Relevance
“…Equally, however, infants and children have their own likes and perceptions of food tastes, which could lead to some type of foods being preferred over others, thereby resulting in variations in isotopic signatures. Perhaps, as Greenwald, Eerkens, and Bartelink () have recently suggested for Central California populations, nonadults in these groups were foraging independently for some portion of their dietary protein. Children can obtain food sources such as grubs, bird eggs of birds, small lizards, fruits, and roots by themselves (i.e., Bird & Bliege Bird, ; Bock, ), engendering variation of isotopic values among nonadults in archaeological populations (Eerkens et al, ).…”
Section: Discussionmentioning
confidence: 83%
“…Equally, however, infants and children have their own likes and perceptions of food tastes, which could lead to some type of foods being preferred over others, thereby resulting in variations in isotopic signatures. Perhaps, as Greenwald, Eerkens, and Bartelink () have recently suggested for Central California populations, nonadults in these groups were foraging independently for some portion of their dietary protein. Children can obtain food sources such as grubs, bird eggs of birds, small lizards, fruits, and roots by themselves (i.e., Bird & Bliege Bird, ; Bock, ), engendering variation of isotopic values among nonadults in archaeological populations (Eerkens et al, ).…”
Section: Discussionmentioning
confidence: 83%
“…Many studies have followed (see Katzenberg, and Tsutaya & Yoneda, for excellent reviews). Within Central California, studies of weaning practices have used bone collagen (Gardner, ; Gardner, Leventhal, Cambra, Bartelink, & Martinez, ) and collagen from tooth dentin (Eerkens & Bartelink, ; Eerkens, Berget, & Bartelink, ; Eerkens, Sullivan, & Greenwald, ; Greenwald, ; Greenwald et al, ; Greenwald, Eerkens, & Bartelink, ; Washburn, ) to understand changing patterns of infant care and maternal investment through time.…”
Section: Introductionmentioning
confidence: 99%
“…First, there are clear dips in both δ 13 C and δ 15 N values around age 9–11 in three of the seven individuals studied here, all females. Although some studies have suggested that metabolic processes associated with normal growth may affect nitrogen isotope fractionation (e.g., D'Ortenzio, Brickley, Schwarcz, & Prowse, ), the fact that others have not found this correlation (Waters‐Rist & Katzenberg, ) suggests that age‐related subsistence practices, particularly supplementation by children of the parentally provisioned diet (Greenwald, Eerkens, & Bartelink, ) or changes in the amount and/or type of dietary protein (Turner, Edwards, Quinn, Kingston, & van Gerven, ), may be behind this pattern. Considering that this is only seen in females in our study around the time of puberty, it may involve certain food restrictions associated with their preparation for adult status.…”
Section: Discussionmentioning
confidence: 99%